2014
DOI: 10.1093/ageing/afu177
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and health service utilisation in the older population: results from The Irish Longitudinal Study on Ageing

Abstract: given these costs and improvements in life expectancy, an increasingly obese older population presents new challenges for healthcare delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
6
17
0
Order By: Relevance
“…The greater uptake of dietetic support observed in this study is consistent with other studies wherein those with class III obesity are more likely to engage with this type of service compared with other allied health supports . Utilization of intensive interventions in isolation was rare, and the greatest proportion of clinically significant weight loss was observed when allied health and intensive interventions were combined.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The greater uptake of dietetic support observed in this study is consistent with other studies wherein those with class III obesity are more likely to engage with this type of service compared with other allied health supports . Utilization of intensive interventions in isolation was rare, and the greatest proportion of clinically significant weight loss was observed when allied health and intensive interventions were combined.…”
Section: Discussionsupporting
confidence: 85%
“…The greater uptake of dietetic support observed in this study is consistent with other studies wherein those with class III obesity are more likely to engage with this type of service compared with other allied health supports. 23 Utilization of intensive interventions in isolation was rare, and the greatest proportion of clinically significant weight loss was observed when allied health and intensive interventions were combined. This is consistent with previous research where multidisciplinary approaches to behavioural interventions were shown to yield greater long-term weight loss and improvement in particular metabolic profiles in patients with comorbid obesity and T2DM.…”
Section: Service Utilizationmentioning
confidence: 99%
“…The figures are lower for men, but nearly 80% in the groups aged 45–54 and 55–64 years had overweight and obesity. This can have implications for the delivery of health services since a large segment of the middle-aged and older adult population will be living with obesity, and obesity is associated with additional health impairments [13]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition obese adults may have physical and social difficulties which inhibit daily living and can also require social care [ 2 ]. Obesity thus has considerable health and social care cost implications [ 3 8 ]. These costs, coupled with the current high prevalence of obesity in the general population (25% of adults in England [ 9 ]) highlight a requirement for effective interventions targeted at obesity prevention and reduction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Local authorities are responsible for social care provision and are perceived to face a considerable cost burden from obesity-related social care costs but there are few published estimates of social care resource use or cost related to BMI levels. Previous studies have been conducted in the older adult populations of Ireland [ 8 ] and Europe [ 13 ]. There is also a lack of published data that directly link obesity with social care need [ 2 ] or enable a calculation of obesity-related social care costs.…”
Section: Introductionmentioning
confidence: 99%